1975
DOI: 10.1073/pnas.72.9.3585
|View full text |Cite
|
Sign up to set email alerts
|

Normal genetically mosaic mice produced from malignant teratocarcinoma cells.

Abstract: 3585The most rigorous test possible for developmental totipotency would be significant contributions of the carcinoma cells to the normal differentiation of virtually all tissues in a mouse. For this to occur, the initially malignant cells would presumably have to be brought into association with early embryo cells so that the latter could provide an organizational framework appropriate for normal development. The experiment is analogous to production of allophenic mice (6).The projected teratoma studies in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
466
0
11

Year Published

1979
1979
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,039 publications
(490 citation statements)
references
References 21 publications
13
466
0
11
Order By: Relevance
“…Results showed that once the embryos were born they were hybrid mice (Mintz and Illmensee, 1975), meaning that some of the offspring cells were derived from normal embryonic tissues and some were derived from the cancerous cells (Mintz and Illmensee, 1975). However, the mice were healthy and tumor-free (Mintz and Illmensee, 1975). This study illustrates the similarities in signaling and communication between the two cell types (Mintz and Illmensee, 1975).…”
Section: Disaccharides: Melibiose and Trehalosementioning
confidence: 74%
See 3 more Smart Citations
“…Results showed that once the embryos were born they were hybrid mice (Mintz and Illmensee, 1975), meaning that some of the offspring cells were derived from normal embryonic tissues and some were derived from the cancerous cells (Mintz and Illmensee, 1975). However, the mice were healthy and tumor-free (Mintz and Illmensee, 1975). This study illustrates the similarities in signaling and communication between the two cell types (Mintz and Illmensee, 1975).…”
Section: Disaccharides: Melibiose and Trehalosementioning
confidence: 74%
“…In this investigation, teratocarcinoma cells were injected into mouse embryos, and the embryos into a mouse surrogate mother (Mintz and Illmensee, 1975). Results showed that once the embryos were born they were hybrid mice (Mintz and Illmensee, 1975), meaning that some of the offspring cells were derived from normal embryonic tissues and some were derived from the cancerous cells (Mintz and Illmensee, 1975). However, the mice were healthy and tumor-free (Mintz and Illmensee, 1975).…”
Section: Disaccharides: Melibiose and Trehalosementioning
confidence: 96%
See 2 more Smart Citations
“…Teratocarcinoma cells are pluripotent and give rise to a variety of differentiated cell types in vivo as well as in culture. When genetically marked teratoma cells are injected into mouse blastocysts they can be recovered in a variety of tissues in the fully developed animals (Mintz & Illmensee, 1975;Papaioannou et al, 1975). These cell-transplantation experiments do not prove that the genetic material of these tumour cells is completely normal, but they certainly show that the tumour-cell phenotype can be reversed when the teratoma cell finds itself in a cellular environment where reprogramming can occur.…”
mentioning
confidence: 99%